Conflict Resolution Of Right to Cultivate Of PT. Sandabi Indah Lestari and The Surrounding Community In Ketahun District, Bengkulu Utara Regency - Dakha Hadi Nugraha; Yeni Widowaty (LPPM Universitas PGRI Sumatera Barat, 2022)
Land conflicts with Cultivation Rights between PT. Sandabi Indah Lestari (PT.SIL) with the people of Ketahun Subdistrict, North Bengkulu Regency, has been going on since 2011. The purpose of this study is to analyze the causes of conflict, conflict resolution methods, and the ideal concept of Cultivation Rights conflict resolution. This study uses empirical juridical research methods. Primary data was obtained from employees of PT. Sandabi Indah Lestari, community planters in Ketahun Subdistrict, North Bengkulu Regency, and the Regional Government. Data was collected using interview methods and documentation. Data analysis by means of descriptive qualitative. The results of this study indicate that the factors that cause land conflicts between PT. Sandabi Indah Lestari with the gardener community, namely the lack of land management by PT. Way Sebayur and PT. Tri Manunggal Pacific Abadi and also the socio-economic factors. Cultivation Rights conflict resolution methods are through mediation, compensation for planting and growing, and employing the surrounding community at PT. Sandabi Indah Lestari, the enclave of Cultivation RightsLand, and legal remedies through the courts. The ideal concept in conflict resolution is sulh, wasatha, and tahkim the concept of sulh which reflects the form of negotiation, especially the negotiation of distributive justice (merger) between PT. Sandabi Indah Lestari and the community for the unfinished Cultivation Rights11 of the former PT Trimanunggal Pacific Abadi.